2017
DOI: 10.1021/acsomega.7b01354
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Biological Responses of Neural Cells and Tissue Interacting with Graphene Oxide Microfibers

Abstract: Neural tissue engineering approaches show increasing promise for the treatment of neural diseases including spinal cord injury, for which an efficient therapy is still missing. Encouraged by both positive findings on the interaction of carbon nanomaterials such as graphene with neural components and the necessity of more efficient guidance structures for neural repair, we herein study the potential of reduced graphene oxide (rGO) microfibers as substrates for neural growth in the injured central neural tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Studies have shown graphene to have great potential as a bioscaffold at the site of the lesion in chronic SCI allowing for neuronal regeneration [ 4 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. GO nanocomposite is considered to be a favorable material for use in treatment because of its unique electro-physico-chemical properties and it is conductivity.…”
Section: Selected Biomaterials That Hold Promise For Future Clinicmentioning
confidence: 99%
“…Studies have shown graphene to have great potential as a bioscaffold at the site of the lesion in chronic SCI allowing for neuronal regeneration [ 4 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. GO nanocomposite is considered to be a favorable material for use in treatment because of its unique electro-physico-chemical properties and it is conductivity.…”
Section: Selected Biomaterials That Hold Promise For Future Clinicmentioning
confidence: 99%
“…These include electrospinning ( 47 , 48 ), capable of producing random- or aligned-nanoscale fibres into mats or scaffolds, providing topographical and morphological cues at a scale matching the extracellular matrix. Wetspinning ( 49 ) and templating ( 50 ) techniques have been used for form cell guides at the micron-scale, allowing the organisation of cells along single fibres compiled into a more complex conduit, while extrusion printing ( 51 , 52 ) has allowed the discrete spatial deposition of graphene-based composites customised for particular cell and tissue types.…”
Section: Bio Fabrication Processesmentioning
confidence: 99%
“…The 3D fabrication of graphene and graphene-composite scaffolds has evolved to include the production of materials with bulk porous properties such as aerogels and foams ( 119 , 172 ), as well as intricately designed structures and architectures produced via electrospinning ( 47 , 48 ), wetspinning ( 49 ), moulding ( 50 , 122 ) and 3D printing ( 123 ) approaches. A composite scaffold of reduced graphene oxide (rGO) and type I collagen was fabricated by depositing a single layer of rGO sheets onto a porous type I collagen template, producing a biodegradable, conductive and biocompatible scaffold ( 119 ).…”
Section: Graphenementioning
confidence: 99%
“…Gonzalez-Mayorga et al fabricated GO microfibers coated with PLL and N-cadherin for NSC implantation, and the newborn neural lineages covered most of the microfiber surface area. These microfibers have also been embedded in hydrogels and implanted at the site of spinal cord injury in rats, and immunofluorescence staining indicated good neural differentiation of NSCs in the perilesional areas, at the material interface, and at the injury site, which suggests the huge potential application of these materials in neural regeneration [46]. In summary, graphene-based fibers, including nanofibers and microfibers, integrate conductivity and implantation properties for enhanced neuronal differentiation, and this along with their good biocompatibility indicates their potential for clinical application in the repair of damaged neurons.…”
Section: 1d Graphene-based Fibersmentioning
confidence: 99%